2013
DOI: 10.1016/j.mrrev.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-targeted effects of ionising radiation—Implications for low dose risk

Abstract: Non-DNA targeted effects of ionizing radiation, which include genomic instability, and a variety of bystander effects including abscopal effects and bystander mediated adaptive response, have raised concerns about the magnitude of low-dose radiation risk. Genomic instability, bystander effects and adaptive responses are powered by fundamental, but not clearly understood systems that maintain tissue homeostasis. Despite excellent research in this field by various groups, there are still gaps in our understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
149
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(160 citation statements)
references
References 211 publications
(269 reference statements)
3
149
0
4
Order By: Relevance
“…Radiation protect are play a due role in normal tissue cells based on the maximum kill tumor cells. Anderson [2] was the first to report injuries of ionizing radiation induced hematopoietic systems, specialists in the later study, found that ionizing radiation can cause T-cells and B-cells reduction rapidly, while the lymphocytes are involved in hematopoietic regulation. Stem cells are survived in the hematopoietic microenvironment, valueadded, differentiated hematopoietic role played.…”
Section: Stem Cells In Mice After Radiation Injury Effect Of Red Bloomentioning
confidence: 99%
“…Radiation protect are play a due role in normal tissue cells based on the maximum kill tumor cells. Anderson [2] was the first to report injuries of ionizing radiation induced hematopoietic systems, specialists in the later study, found that ionizing radiation can cause T-cells and B-cells reduction rapidly, while the lymphocytes are involved in hematopoietic regulation. Stem cells are survived in the hematopoietic microenvironment, valueadded, differentiated hematopoietic role played.…”
Section: Stem Cells In Mice After Radiation Injury Effect Of Red Bloomentioning
confidence: 99%
“…According to a widely accepted definition, very high doses of radiation are over 15 Gy; high doses range between 5 and 15 Gy; medium doses between 0.5 and 5 Gy; and low doses between 0.05-0.5 Gy. 15 Adjuvant therapy is performed by treating patients with very high/high radiation doses, which are divided into multiple smaller doses given over a period of one to 2 months. 16 Non-target areas of therapy may receive a lower amount of radiation that is not easily quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, ionizing radiation (IR), even at low dose may be harmful and can cause dangerous events in biological systems (Kadhim et al, 2013). An increased dose is always harmful.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, a particular radiation may act by different mechanistic pathways (Yang et al, 2012). Low doses (0.05 to 0.5 Gy) of IR can cause genomic instability, such as chromosomal alterations and cell death (Kadhim et al, 2013), and can lead to a double failure of DNA and epigenetic alterations in histones (Sasakil et al, 2014). Studies with mass spectrometry based on proteome analysis in human skin model, indicated that after 48 h exposure to 3, 10, and 200 cGy x-rays alter and disrupt 135 proteins, where carboxipeptidases and ubiquitin carboxyl terminus isoenzyme hydrolase were the most sensitive, indicating that radiations at any dose can alter enzymatic proteins (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%